Uretrolitíase obstrutiva em equino - Almeida e Macêdo, Juliana Targino Silva; Biscarde, Carmo Emanuel Almeida; Nascimento, Karla Alvarenga; Ferreira Júnior, Jair Alves; Pedroso, Pedro Miguel Ocampos (Acta Scientiae Veterinariae, 2017)
Background: The presence of macroscopic concretions in the urinary system is called urolithiasis. In horses the occurrence is rare. The calculi are generally large and unique spicule concretions, composed of calcium carbonate crystals. Less commonly, the concretions are of mixed crystals of calcium carbonate and of calcium phosphate. The aim of the this work was to report a case of obstructive urethrolithiasis in a horse. Case: A 1-year-and-5-month-old, undefined breed, uncastrated male presented tenesmus, strangury, and dysuria. The horse died seven days after the onset of clinical signs and was referred for necropsy. At necropsy, samples were collected from organs of the abdominal cavity, thoracic cavity, central nervous system and integumentary system. The fragments were fixed in 10% formaldehyde, cleaved, routinely processed for histology and stained with hematoxylin and eosin. A urinary calculus collected during necropsy was sent for chemical analysis. In the abdominal cavity, a large quantity of citrus liquid of uremic odor was observed. Deposition of fibrin filaments in the peritoneum was observed, as well as in diaphragm and abdominal organs. Serosa of the small and large intestine was red with evidence of the capillaries. Kidneys presented multiple slightly protrusive white areas with a maximum diameter of 3 mm. When cutting, these areas were limited to the cortical region. There was rupture of the urinary bladder, diffuse loss of the mucosa with capillary exposure and evidence, as well as the deposition of fibrin and crude blood clots. The opening of the penile urethra presented a urolith of approximately 3.5 x 3 cm in size, with a rough and porous surface, light brown and of a stony consistency. Necrosis of the mucosa and hemorrhage were also observed in the urethra. Microscopically, the kidney showed multiple foci formed by intense inflammatory infiltrate composed of macrophages, neutrophils and plasma cells in the interstitium of the cortical region. In the urinary bladder, there was diffuse necrosis of the lining epithelium, marked inflammatory infiltrate composed mainly of neutrophils in the submucosa, in addition to fibrin deposition and edema. Penile urethra presented changes similar to those described in the urinary bladder. The chemical analysis of the urinary calculus demonstrated the presence of calcium oxalate, triple magnesium ammonia (struvite) phosphate and ammonium in its composition. Discussion: The diagnosis of obstructive urethrolithiasis was established from the clinical-pathological condition. The occurrence of urolithiasis in horses is rare. The lower occurrence in this species is probably attributed to the large amount of mucus produced by the glands in the renal pelvis and the proximal ureter, which acts as a lubricant to prevent the adhesion of the crystals to the urothelium. The absence of sigmoid flexure and vermiform urethral process in equine also influence the low occurrence of the disease, when compared to ruminants. Rupture of the urinary bladder followed by uroperitonitis and nephritis as observed in this case are common consequences in obstructive urolithiasis. Uroliths in equines are generally composed of a variety of hydrated calcium salts and calcium carbonate, magnesium, and phosphorus salts, with less common struvite compounds. Urethrolithiasis is poorly described in horses and can be caused by struvite stones.